INTERACTIONS OF XANTHONE COMPOUNDS FROM THE MANGOSTEEN (GARCINIA MANGOSTANA L) PERICARPS AGAINST INOS, COX-1, AND COX-2 ENZYME RECEPTORS AS ANTI-INFLAMMATORY - LESTARI, DWINTHA; SARI, RISKA PERMATA; MUSFIROH, IDA; MEGANTARA, SANDRA; PRACEKA, MEILINDA SETYA; KHAIRUL IKRAM, NUR KUSAIRA; MUCHTARIDI (International Journal of Applied Pharmaceutics, 2023)
Objective: Mangosteen is a plant that is very effective for inflammation. Besides that, the skin of the mangosteen plant in Indonesia continues to be developed because it is an antioxidant and suppresses the production of cytokines. Methods: Screening pharmacophores and molecular docking simulations by molecular modeling computation to predict the activity of the Mangosteen plant in silico and to determine potential drug candidates from mangosteen for inflammation to the iNOS, COX-1, and COX-2. Results: Pharmacophore Screening, γ-mangosteen has the highest pharmacophore fit score of 33.32 and 33.64 on COX-1 and COX-2 and is selective to iNOS target. Molecular docking of α-mangosteen and γ-mangosteen test compounds to the active site of used, COX-1, and COX-2 enzymes showed free energy binding (ΔG °) values of,-5.09,-5.00,-6.15; and-6.76,-5.30,-7.81 Kcal/mol respectively. Meanwhile, hydrogen bonds and good ΔG ° values ​​were formed between γ-mangosteen and COX-2, where the Hydroxyl group on γ-mangosteen interacted with the amino acids His75, Ser339, and Ala513 with ΔG ° of-7.81 Kcal/mol. Conclusion: It can be said that α-mangosteen and γ-mangosteen have molecular interactions with COX-1 and COX-2 active sites with the highest affinity for COX-2 compared to COX-1, and iNOS.